Mycorrhizas as a tool for ecological restoration - Carrillo-Saucedo, Silvia Margarita; Puente-Rivera, Jonathan; Montes-Recinas, Saraí; Cruz-Ortega, Rocío (Instituto de Ecología, A.C., 2022)
Background and Aims: Mycorrhizae are symbiotic associations between mycorrhiza fungi and plant roots. The plant interchanges photosynthates for nutrients, which the fungus obtains from the soil, such as nitrogen and phosphorus. Mycorrhizae plants are more resistant to infection by pathogens, tolerate stress better, and also promote soil conservation. The main purpose of this work was to analyze the general aspects of mycorrhizal symbiosis of species native to Mexico, to be used as a tool for soil recovery Methods: A comprehensive review of 140 original articles, experimental and synthesis papers published between 1984 and 2019 was carried out. Studies performed in Mexico with native species and with information on the different inoculation methods reported, and with ecological relevance were selected. The databases searched were Scopus, Web of Science, Crop Protection Compendium Database, Forest Science Database, PubMed and SciELO. Keywords were: "mycorrhizae", "endo and ectomycorrhizae", "ectomycorrhizaes and Pinus", "ectomycorrhizae and Quercus", "mycorrhizae inoculation", "ectomycorrhizae and ecological restoration", and “ectomycorrhiza and Mexico”. Related research protocols, thesis, or patents were searched. Key results: The results of the literature review were structured and discussed in six sections, including general characteristics of the mycorrizal association, general methods of inoculation, symbiotic complex, impact of mycorrization in temperate ecosystems restauration, important aspects for the symbiosis establishment, as well as some examples of ectomycorrizhae and arbuscular mycorrizhal fungi in temperate forest. Conclusions: This review highlights the importance of deepening the knowledge of the potential that mycorrhizal association have as a tool in ecological rehabilitation and recuperation of deforestated and perturbed temperate zones.